Kelayakan Usaha Pengawetan Bambu Berbasis Masyarakat - Haris Prasetyo (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Bamboo can be used as a wood substitute, but bamboo has a low natural durability. Traditional methods of preservation bamboo by water soaking takes a long time and vast place. The low natural durability of bamboo and the low contribution of household income from bamboo cultivation encourages the development of other business alternatives, such as bamboo preservation business. The objectives of this research are to assess the feasibility of bamboo preservation. Data analysis was performed using Market Analysis and Development (MA&D) method. The results of market aspect shows that bamboo is feasible to be developed due to the large market demand still not balanced with limited availability. The results of ecological and environmental aspects, need to find alternative preservatives that are more environmentally friendly. The results of social and institution aspect shows that bamboo business has the support of local government and the community also has local wisdom in the management of bamboo. The results of financial analysis shows that in riil condition bamboo preservation business was feasible; Net Present Value (NPV) is IDR 30.737.598, Benefit Cost Ratio (BCR) at 1,29 and the Internal Rate of Return (IRR) at 31,72%.